2017
DOI: 10.1007/s10508-017-1105-3
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Condomless Sex Among Men Who Have Sex with Men Living with HIV: A Curvilinear Association

Abstract: Depressive symptoms are highly prevalent among HIV-positive men who have sex with men (MSM) and may contribute to risky health behaviors. However, research linking depressed mood to condomless sex in HIV-positive MSM has yielded mixed findings and has focused primarily on testing for a linear association. In the current study, we tested both linear and curvilinear models to assess the association of depressive symptoms to condomless anal sex for the most recent sexual episode in a sample of MSM living with HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Another strength of our study is that we examined the curvilinear time effects, which allow for a more accurate presentation of WIB over multiple years. Previous research appears overly reliant on statistical methods that assume a linear relationship between continuous predictors and logit of outcome in a logistic regression, which obscures the curvilinear patterns of predictors and renders their models less representative for actual data [29]. In addition, our analyses on "change of points" integrates measures of interest using polynomial terms, which is suggested to unveil useful information for policy makers and practitioners [30].…”
Section: Limitations and Strengthmentioning
confidence: 99%
“…Another strength of our study is that we examined the curvilinear time effects, which allow for a more accurate presentation of WIB over multiple years. Previous research appears overly reliant on statistical methods that assume a linear relationship between continuous predictors and logit of outcome in a logistic regression, which obscures the curvilinear patterns of predictors and renders their models less representative for actual data [29]. In addition, our analyses on "change of points" integrates measures of interest using polynomial terms, which is suggested to unveil useful information for policy makers and practitioners [30].…”
Section: Limitations and Strengthmentioning
confidence: 99%
“…It is generally acknowledged that positive affect can increase sexual arousal and sexual desire and therefore facilitate sexual behavior [23]. In contrast, the MSM with negative emotions may use sex as a mood regulator and may practice more condomless anal sex with casual partners [27,[73][74][75]. One possible explanation for this finding is that health-compromising behaviors (eg, unprotected sex) may be used as coping mechanisms to manage the effects of negative emotions.…”
Section: Principal Findingsmentioning
confidence: 99%
“…For example, anxiety has been found to facilitate genital responses [26], whereas another study suggested that individuals who experienced negative emotions practiced fewer sexual behaviors than those who had positive emotions [25,26]. In the studies of MSM, those with depression or higher negative affect are more likely to practice condomless anal intercourse or have multiple sexual partners [27][28][29]. Researchers have revealed that affective states may influence the health status among MSM.…”
Section: Introductionmentioning
confidence: 99%
“…1 Nevertheless, estimates from 2011 to 2015 have shown the number of new cases of HIV among MSM have remained constant at about 26,000 per year. 2 Additionally, depressive symptoms 3,4 and substance use [5][6][7] are major public health issues affecting MSM living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature shows that an association between age and depressive symptoms and substance use has been found among MSM living with HIV. 3,10,11 Age has been shown to be negatively associated with drug use. 11 However, this study was conducted in the UK.…”
Section: Introductionmentioning
confidence: 99%